Currency Volatilities of BRICS Countries: The Impact of Commodity Prices, Interest Rates and Geopolitical Risks - Luo, Heng (University of the Witwatersrand, Johannesburg, 2024)
Currency volatility in emerging markets is an interesting topic for managers, investors, and regulators. This study investigated the currency volatility of the five BRICS nations, examined the risk sources of the BRICS currencies and observed the connectedness of their currency risks, in the context of the COVID-19 pandemic, Russia-Ukraine war and current interest rate hikes, using data spanning between September 2011 and September 2023. The ARDL model was the main econometrics approach applied for identifying the long run and short run currency volatility determinants. In addition, Quantile Regression was adopted to observe the currency markets’ tail behaviours. The research has three major findings. Firstly, the research confirmed that interest risk, commodity risks, geopolitical risk, and economic policy uncertainty are the risk sources of BRICS nations’ currencies, especially when volatilities are at high levels. Additionally, the research provided support for spillover of the commodity market, the USA’s geopolitical risks and economic policy risks to the BRICS’ currency markets, and the volatility spillover across BRICS currency markets. Finally, the study revealed the shock evolution trend of Chinese RMB, with accelerating impacts of US geopolitical risk, US and home economic policy risk, and oil price exposure on RMB’s volatility. Overall, the heterogeneity of BRICS nations’ currency markets responding to external shocks, and the asymmetry of the connectedness of BRICS currency markets, were important implications of the research. The findings are crucial for investors and policy makers
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; BRICS; Currency; Economic Policy Uncertainty; Commodity; Interest rate; SDG-8: Decent work and economic growth